ANALISIS POTENSI PEMANENAN AIR HUJAN SEBAGAI SUBSTITUSI KEBUTUHAN AIR NON-POTABLE PADA GEDUNG PERKANTORAN BERTINGKAT DI SURABAYA - Immanuel Surya Pratama; Nur Latifah Khomsiati; Dieksa Saputri Himawan; Fadilatul Anisa; Tee Tze Kiong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The limited supply of clean water in urban areas necessitates the development of efficient and sustainable alternative solutions. Rainwater harvesting is a promising approach to reduce dependence on conventional clean water sources in multi-story buildings. This study aims to assess the potential of rainwater haversting as a substitute for non-potable water needs in multi-stoty office buildings in urban areas. The methods employed include ten year rainfall data analysis (2013-2023), effective rooftop area calculation, storage volume situation, and building water demand analysis. The result indicate that with an effective roof area of 1.200 m2 and an avarge annual rainfall of 2.100 mm, the rainwater haversting system can fulfill 42-67% of non-potable water demands, primarily for toilet flushing, garden irrigation, and fire supression. Economic analysis reveals a payback period of 6 year 8 month with annual water cost savings of IDR 18.400.000,00. This research contributes of the development of green buildings and water conservation in urban environments.